Comparison of the effectiveness of vitrectomy with silicone oil or perfluoropropane tamponade for myopic foveoschisis with foveal detachment - Dan, Handong; Wang, Dongdong; Huang, Zixu; Liu, Yizong; Hou, Huiming; Jin, Yujia; Song, Zongming (Frontiers in Medicine, 2025)
IntroductionVitrectomy with silicone oil or perfluoropropane (C3F8) tamponade is a standard of treatment for myopic foveoschisis with foveal detachment (MFFD). In this study, we compared the pre- and postoperative best-corrected visual acuity (BCVA) and maximum foveal thickness (MaxFT) of patients with MFFD who underwent vitrectomy with silicone oil or C3F8 tamponade.MethodsAll patients underwent comprehensive ophthalmological examinations, including measurement of BCVA, axial measurement, optometry, intraocular pressure, slit-lamp examination, fundus examination, and optical coherence tomography. Patients with MFFD were divided into two groups. All patients underwent with 23-gauge pars plana vitrectomy with fovea-sparing internal limiting membrane peeling, and fluid-air exchange. One group underwent tamponade with silicone oil, whereas the other group underwent tamponade with C3F8. The silicone oil was completely removed upon complete resolution of MFFD. Phacoemulsification with intraocular lens implantation was performed when a lens opacity was noted during vitrectomy or along with silicone oil removal. BCVA and MaxFT were assessed at 1, 3, 6, and 12-months post-operatively. Patients with silicone oil were additionally assessed 3-months after silicone oil removal. All data were calculated using GraphPad Prism.ResultsForty-one patients with 41 eyes were enrolled in the study. Eighteen eyes were included in the silicone oil group, whereas 23 eyes were included in the C3F8 group. Both groups demonstrated significant improvement in BCVA and MaxFT at 1, 3, 6, and 12-months post-operatively. There was no significant difference in BCVA and MaxFT between both groups post-operatively. Transient ocular hypertension was noted in six and three cases in the silicone oil and C3F8 groups, respectively. One case in the C3F8 group developed a macular hole. There were no other complications in the two groups.ConclusionVitrectomy with fovea-sparing internal limiting membrane peeling, and silicone oil or C3F8 tamponade are effective and practical treatment options for MFFD.